Radioassay of the materials for AMoRE-II experiment - Agrawal, A.; Alenkov, V. V.; Aryal, P.; Bae, H.; Beyer, J.; Bhandari, B.; Boiko, R. S.; Boonin, K.; Buzanov, O.; Byeon, C. R.; Chanthima, N.; Cheoun, M. K.; et al. (Frontiers in Physics, 2024)
The AMoRE-II experiment will search for the 0νββ decay of 100 Mo nuclei using molybdate crystal scintillators, operating at milli-Kelvin (mK) temperatures, with a total of 80 kg of 100 Mo. The background goal for the experiment is 10 -4 counts/keV/kg/year in the region of interest around the 0νββ decay Q-value of 3034 keV. To achieve this level, the rate of background signals arising from emissions produced by decays of radioactive impurities in the detector and shielding materials must be strictly controlled. To do this, concentrations of such impurities are measured and are controlled through materials selection and purification. In this paper, we describe the design and 1 the construction materials used to build the AMoRE-II detector and shielding system, including active and passive shielding, the cryostat, and the detector holders and instrumentation, and we report on measurements of radioactive impurities within candidate and selected materials.